Using the SUS to Help Demonstrate Usability's Value to Business Goals. (September 2013) - Bangor, Aaron; Joseph, Kurt; Sweeney-Dillon, Marian; Stettler, Garrett; Pratt, James
As part of an effort to connect results of human factors testing with the needs of internal business clients, a usability testing program was created for smartphones to establish a link between usability metrics and business indicators of success in the marketplace. In addition to standard usability metrics of effectiveness, efficiency, and satisfaction (ISO, 1998), a measure of hedonics (Hassenzahl, Beu, and Burmester, 2001) was used. Of particular note was the use of the System Usability Scale (SUS) (Brooke, 1996) to provide a single measure of user satisfaction for all smartphones tested. Data from 54 studies involving 872 participants were analyzed to determine if usability metrics predicted marketplace outcomes. Results show that usability metrics are significantly correlated with indicators of business success and that the SUS accounted for most of usability's contribution. Discussion of these results, the value of SUS, and implications for usability professionals are discussed.